PS 17-57 PREVALENCE AND CLINICAL CORRELATES OF MICROALBUMINURIA IN KOREAN PATIENT WITH ESSENTIAL HYPERTENSION. (September 2016) - Yoo, Byungsu; Son, Jung Woo; Kim, Jang Young; Ryu, Kyu Hyung; Han, Seong Woo; Choi, Seok Won; Shin, Miseung; Kim, Eung Ju
Abstract : Objective: The prevalence of microalbuminuria and its relationship with several cardiovascular risk factors and target organ damage is very important. However, data from Asian population including Korea are rare. We evaluate the prevalence and clinical correlates of microalbuminuria in korean patient with essential Hypertension. Design and method: The Korean hypertension registry (KorHR) is an on-going prospective multicenter cohort study for hypertension. Inclusion criteria are as follows: Consecutive patients with essential hypertension, Aged more than 30 years old, Consent to registry enrollment, Incident hypertensives, Hypertensive patients without definite cardiovascular damage such as coronary artery, renal, cerebral artery disease and evidence of definite target organ damage, Hypertensive patients who visited the research hospital for the first time within 5 years. We will follow study patients up to at least 3 years and investigate the occurrence of major cardiovascular events and mortality. As of Jan 2016, the interim analysis of 1, 318 consecutive subjects was performed to understand the baseline characteristics of the population. Microalbuminuria (MAU) was defined as the albumin-to-creatinine ratio in first morning urine samples. Results: Of all cohort patients, we selected 778 patients without missing value. The mean age is 51.5 ± 12.2 year old and male is 63%. 55.7% is no evidence of medical treatment for hypertension. Mean office SBP / DBP was 143.40 ± 20.83 / 87.83 ± 15.87 mmHg. Mean body weight is 71.24 ± 13.27 kg, waist is 77.90 ± 30.65 and BMI is 26.05 ± 3.46. The distributions of risk factors are follows: Diabetes (6.2%), dyslipidemia (41%), family history of coronary heart diease (41%) and current smoking (19%). The prevalence of microalbuminuria was 12.4%. Comparing of prevalence of MAU between never treated patients and on-treatment patient, Never-treated patients were more likely to be patients with MAU (16.5 % vs. 7.3%, p < 0.05). Regression analysis demonstrated that age and uric acid and the presence of on-treatment significantly influence albuminuria and together account for a large part of its variations. Also, Uric acid was significantly related to age, sex and presence of on- treatment. Conclusions: The prevalence of microalbuminuria in essential hypertension is lower than previously reported. Increased urinary albumin excretion is associated with old age and under-treament of hypertension.